Penerapan Metode Drill and Practice Dalam Upaya Meningkatkan Hasil Belajar Pendidikan Agama - Huproni Huproni (Sustainable, 2020)
This study aims to improve student learning outcomes through the use of drill and practice models in Islamic studies in class XII IPS 3 at SMAN 1 Pusakagara. This research is a descriptive qualitative research with a sample population of 36 students consisting of 21 male students and 15 female students, data obtained through interviews, tests, and observations. From the test data in the first cycle, the student learning outcomes who completed were 22 students with an average score of 69 and the highest score was 85, while the lowest score was around 45. In the second cycle, student learning outcomes who completed an increase even though the number was not so significant. Of the 36 students who are in the upper class, there are about 26 students and 10 students in the lower class, the highest score is 87 and the lowest score is 51 with a standard deviation of 9. By using the drill and practice learning model in Islamic studies in Class XII IPS 3 at SMAN 1 Pusakagara has improved student learning outcomes when compared to teachers who teach using the lecture method.